In vitro culture establishment and shoot regeneration in rubber (Hevea brasiliensis Muell. Arg.) - Moradpour, Mahdi (2015)
The development of in vitro methods to produce high quality clonal planting materials of Hevea brasiliensis for replanting and new planting is highly desirable and essential. Some procedures do exist but generally do not address well the initial stage of culture establishment. The establishment of in vitro cultures of challenging woody plant species like H. brasiliensis have frequently been hampered by persistent microbial contamination, phenolic production, phase change and low response to media. Therefore, the overall goal of this study was to establish an efficient in vitro propagation method for H. brasiliensis through solving the persistent microbial contamination problems, controlling phenolic production and increasing the response of explants to media. Shoot tips and axillary buds derived from one to two year-old grafted plants of H. brasiliensis clone RRIM 2025 were used as explants. In determining the most suitable method of reducing explant contamination, different concentrations of sodium hypochlorite, mercuric chloride and nano silver at different immersion times were assessed on explants derived from three physiological leaf stages (bronze, light green and stable green leaf stages) of preculture and non-preculture treated plants. The highest percentage of survival (94.44%) was from explants derived from the light green leaf stage of preculture treated plants immersed in 92.6 μM NS for 20 min. Different types of adsorbents which were silver nitrate, activated charcoal and nano silver were assessed in controlling browning of in vitro cultures of H. brasiliensis. Nano silver at 37.04 μM significantly produced the highest percentage of explant survival (87.03%) with a low percentage of browning (10%). In an attempt to determine the most suitable medium for in vitro culture of H. brasiliensis explants, Murashige and Skoog (MS) medium, Woody Plant medium (WPM) and MB medium in combination with 3%, 6% and 9% sucrose concentrations were assessed. After 16 weeks of culture, the highest percentage of shoot formation (80%) was on MB medium with 6% sucrose. In evaluating the effects of benzyl aminopurine (BAP) alone on shoot induction of H. brasiliensis, the highest percentage of axillary shoot emergence (61.11%) was obtained on MB medium containing 22.2 μM BAP after 16 weeks of culture. In the second experiment on shoot induction, different concentrations of BAP in combination with 1.44 μM Gibberellic acid (GA3) were assessed whereby MB medium containing 22.2 μM BAP with 1.44 μM GA3 produced a maximum mean number of 2 shoots per explant after 16 weeks of culture. Lastly, different concentrations of BAP in combination with 2.7 μM naphthalene acetic acid (NAA) were assessed on shoot induction whereby the highest mean number of 3 shoots per explant were obtained on MB medium supplemented 8.8 μM BAP and 2.7 μM NAA after 16 weeks of culture. In the study on multiplication and elongation of H. brasiliensis shoots, various combinations of plant growth regulators were assessed. In the first experiment, different concentrations of GA3 in combination with 2.2 μM BAP and 1.23 μM indole-3-butyric acid (IBA) were tested and a maximum mean number of 10 shoots was produced on MB medium supplemented with 1.45 μM GA3, 2.2 μM BAP and 1.23 μM IBA after 16 weeks of culture. In the second shoot multiplication experiment, in vitro shoots were placed in different concentrations of thidiazuron (TDZ) combined with 0.1 μM IBA and the highest mean number of shoots per explant (4.6) was obtained on MB medium containing 0.45 μM TDZ and 0.1 μM IBA after 16 weeks of culture, Finally, different concentrations of kinetin (Kin) in combination with 4.4 μM BAP and 2.7 μM NAA were tested for shoot multiplication and a maximum mean number of 4.33 shoots, which were strong and healthy, was obtained on MB medium supplemented with 9.3 μM Kin, 4.4 μM BAP and 2.7 μM NAA. In conclusion, this study indicates that a successful establishment of in vitro culture of H. brasiliensis requires the understanding of the species leaf developmental stages, the interaction of the explant source with the environment and the effective application of the non-toxic silver nano particles in reducing microbial contamination and browning of Hevea explants. An efficient initial culture establishment developed in this study thus opens the way for future application of the microcutting technique for propagation as well as genetic improvement of H. brasiliensis.